2012
DOI: 10.1038/am.2012.50
|View full text |Cite
|
Sign up to set email alerts
|

Configurable 2D and 3D spheroid tissue cultures on bioengineered surfaces with acquisition of epithelial–mesenchymal transition characteristics

Abstract: Both two-dimensional (2D) and three-dimensional (3D) biomaterial-based culture platforms that are capable of mimicking the in vivo microenvironment to recapitulate the physiological conditions are vital tools in a wide range of cellular and clinical research. Here we report tissue cultures in a microfluidic chip that allows deterministic patterning of cells in 2D/3D. The chip contains a cell-supporting membrane bioengineered to attain either 2D or 3D cell patterns by selectable deposition of extracellular matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…In turn, the enhanced communication influences a number of important cellular functions such as migration, invasion, proliferation, apoptosis and differentiation 209 . It was, for example, shown by Kuo et al that the epithelialmesenchymal-transition, which is a hallmark in the metastatic process, is promoted for several cancer cell lines when they are cultured as spheres 210 . Thus, it can be concluded that the cultivation conditions have a major influence on the cellular phenotype and function and that cellular responses following NP exposure are therefore likely to be drastically altered in a 3D model when compared to a conventional monolayer 207 .…”
Section: The Effect Of a 3d Environmentmentioning
confidence: 99%
“…In turn, the enhanced communication influences a number of important cellular functions such as migration, invasion, proliferation, apoptosis and differentiation 209 . It was, for example, shown by Kuo et al that the epithelialmesenchymal-transition, which is a hallmark in the metastatic process, is promoted for several cancer cell lines when they are cultured as spheres 210 . Thus, it can be concluded that the cultivation conditions have a major influence on the cellular phenotype and function and that cellular responses following NP exposure are therefore likely to be drastically altered in a 3D model when compared to a conventional monolayer 207 .…”
Section: The Effect Of a 3d Environmentmentioning
confidence: 99%
“…Kuo et al reported a size standard deviation of 104% for on dish liquid overlay and 13% for on-chip spheroid diameters [129]. This illustrated that the spheroid size was much more uniform in the microfluidic approach in comparison with that in the liquid overlay technique.…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, PBS and culture medium were introduced to wash away unbound collagen. 100 ll of HEK 293T cells ($1.5 Â 10 3 cells) in culture medium were perfused into the top channel by tuning the solution level height as described, 8 and the device was placed in a 5% CO 2 incubator at 37 C overnight to enable cell attachment and spread on the membrane. Subsequently, Tet was introduced into the bottom channel at t ¼ 0 h, as on-device experiments.…”
Section: Operational Procedures For the Microfluidically Tet Inducmentioning
confidence: 99%